Effect of maximal versus supra-maximal exhausting race on lipid peroxidation, antioxidant activity and muscle-damage biomarkers in long-distance and middle-distance runners - Mohamed, S.; Lamya, N.; Hamda, M. (Asian Journal of Sports Medicine, 2016)
Background: Exhausting physical exercise increases lipid peroxidation and causes important muscle damages. The human body tries to mitigate these adverse effects by mobilizing its antioxidant defenses.